Ansiedad y su afectación en el área emocional en una adolescente de 15 años de la ciudad de Babahoyo - Rivadeneira Velasco, Tahiri Anabel (2022)
The present work "Anxiety and its affectation in the emotional area in a 15-year-old adolescent", was based on the fact that anxiety is excessive worry and fear, recurring towards the future, where negative, positive or neutral emotions are involved. A methodology with a qualitative descriptive approach with a quasi-experimental design was used, in which various techniques were implemented to obtain information, among them are clinical observation, semi-structured interview using clinical history as an instrument for data collection, psychometric batteries , for example, Beck Anxiety Inventory (BAI), Traumatic Experiences Questionnaire (TQ), Bandelow Panic and Agoraphobia Scale (PAS), which were very useful to corroborate the patient's presumptive diagnosis, which it was verified through the diagnostic manuals, such as the DSM-V (300.01) Panic disorder and the ICD-10 (F41.0) Panic disorder (episodic paroxysmal anxiety). Among the findings detected, it was found that, from the surprise home invasion by the police, due to this the pubertal began to have panic attacks, as well as difficulty answering phone calls from strangers, especially if they are from mens. Finally, psychotherapeutic techniques based on Cognitive-Behavioral Therapy were proposed, where cognitive restructuring was applied, therefore, it is expected that in the following sessions or in the future the 4-stroke breathing techniques and passive relaxation will be applied, since that will allow you to control your symptoms.